Obsession of Liminality: Religious and Cultural Contamination during Midlife Transition - Muhamad, R.; Yunus, N. A.; Asrenee, A. R.; Mohd Ali, Z. (Science Forecast, 2019)
Obsessive-compulsive disorder (OCD) is a common psychiatric disorder with a bimodal age of onset where the later onset is commonly associated with higher depressive and anxiety rates. We present a case of OCD during midlife transitional phase which was hiding inside the full-blown depression where religious and cultural factors had arguably shielded the presentation of OCD. The obsession of religion had been regarded as a normal change for aging; hence, its treatment was overlooked. In this paper, we argue that collaborative consultation between family physicians, psychiatrists and religious scholars would be crucial in providing holistic care for OCD patients. We also call for physicians to be more proactive in the assessment and prevention of mental illnesses by providing treatment and care for members of the society on how to live in liminal stages of life.